Thermal Performance of Oil Palm Fibre and Paper Pulp as the Insulation Materials - S.H., Ibrahim; Sia, W.K.; A., Baharun; M.N.M., Nawi; R., Affandi (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Energy consumption for residential use in Malaysia is keep increasing yearly in order to maintain the internal thermal comfort of the building. Roof insulation material plays a vital role in improving the thermal comforts of the building while reduce the cooling load of the building. Oil palm industry in Malaysia had grown aggressively over the past few decades. Tons of oil palm waste had produced during the process such as empty fruit bunch fiber. Another waste material that available and easy to obtain is paper. Paper is a valuable material that can be recycled. Waste paper comes from different sources such as newspaper, office and printing papers. This study will take advantage of the available resources which could contribute to reduce the environment impact. The aim of this study is to investigate the thermal performance of roof insulation materials using mixture of oil palm fiber and paper pulp with different ratio and thickness. This study found that the thermal performance of the paper pulp is slightly better compare to the oil palm fiber. Thermal conductivity of the particle board reduces around 4.1% by adding the 10% of paper pulp into the total density of the particle board. By adding 75% of paper pulp, the thermal conductivity of the particle board could be reduced to 24.6% compare to the oil palm fiber board under the similar condition. Therefore, from this study, it could be concluded that paper pulp has high potential to be used as a building insulation material.